First data on ostracods and foraminifera living in Cystoseira associations in western Ionian Sea - SCIUTO, FRANCESCO; ROSSO, ANTONIETTA; SANFILIPPO, ROSSANA; ALONGI, GIUSEPPINA; CATRA, MARCELLO; SERIO, DONATELLA; BEJAOUI, SAMEH; LEONARDI, RICCARDO; VIOLA, ALFIO (Mediterranean Marine Science, 2018)
For the first time ostracod and foraminifera populations living on infralittoral algae were analysed from three different localities near the Ciclopi Islands Marine Protected Area along the Etnean Ionian coast of Sicily, few km N of the city of Catania. Six series of samples, each of three samples, were collected at 5, 10 and 26 m water depth in sea bottom areas where the Biocoenosis of the Infralittoral Algae is developed. Some samples were collected inside the Ciclopi Islands Marine Protected Area (CIMPA) and some outside it. In all the samples the ostracod association is characteristically constituted by a mixture of true shallow water phytal taxa and and infralittoral sediment-dwelling taxa. The family Xestoleberididae is markedly dominant, mainly in the shallowest samples. Xestoleberis dispar represents more than 60% of all the specimens, followed by X. communis and X. dispar. The families Paradoxostomatidae (with Paradoxostoma rarum, P. simile, P. parallelum, P. intermedium, P. atrum and P. caecum), Hemicytheridae (with Aurila prasina and A. convexa), Bairdidae (with Neonesidea mediterranea, N. corpulenta, and N. Longevaginata) follow. Loxoconchidae (with Loxoconcha rhomboidea), Pontocyprididae (with Pontocypris mediterranea and Pontocypris pirifera) and Cytheruridae (with very few specimens of Semicytherura spp.) are subordinate. Foraminifera are represented almost exclusively by phytal benthic taxa. Between them the the family Miliolidae is markedly prevalent, mostly represented by Quinqueloculina species, followed by the family Rotaliidae with Elphidium crispum, E. depressum, E. aculeatum, and Elphidium spp. Discorbidae, with Rosalina spp.; Cibidididae, largely represented by Cibicides refulgens and C. advenum; Planorbulinidae with Planorbulina mediterranensis, are also present.